2009
DOI: 10.3109/02770900902779284
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ambient Ozone Exposure with Airway Inflammation and Allergy in Adults with Asthma

Abstract: In adults with asthma but not controls studied during peak ozone season, increasing ozone exposure predicted lower lung function and increased biomarkers of respiratory and systemic inflammation. These associations were enhanced in atopic participants, both with and without asthma. Importantly, the study findings were noted while atmospheric ozone levels were predominantly within the current and revised national air quality standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Several studies have found stronger associations in individuals with asthma or COPD (6,9,13,35,36), although many have found associations between air pollution and lung function in normal subjects (5)(6)(7)(8). Only 20% of our study population met our definition of asthma/COPD, and thus our power to detect susceptibility in this subgroup was limited.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies have found stronger associations in individuals with asthma or COPD (6,9,13,35,36), although many have found associations between air pollution and lung function in normal subjects (5)(6)(7)(8). Only 20% of our study population met our definition of asthma/COPD, and thus our power to detect susceptibility in this subgroup was limited.…”
Section: Discussionmentioning
confidence: 70%
“…This result was similar to the results of a previous study. 15 On the other hand, Modig et al recently reported that the effect of NO 2 on FeNO was stronger than the effect of O 3 in subjects with asthma. 36 …”
Section: Discussionmentioning
confidence: 97%
“…14 In addition, elevated O 3 levels were reported to be associated with airway inflammation in atopic participants, both with and without asthma. 15 While some findings have shown the acute effects of O 3 on respiratory symptoms, the pathophysiological mechanisms for the effects of O 3 are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…33 Other investigators report that atopic individuals, even those without asthma, had enhanced inflammatory responses to inhaled O 3 compared to healthy subjects at O 3 levels within current NAAQS standards. 34,35 associations between clinical and subclinical manifestations of adverse pulmonary health effects and exposure to ambient air pollutants while providing some indication of potential mechanisms involved.…”
Section: Ambient Air Pollutionmentioning
confidence: 99%